B01 The effect of sleep on swimming performance - Dawson, Phoebe; Burnie, Louise (Graduate Journal of Sports Science, Coaching, Management, & Rehabilitation, 2024)
There has been extensive research on sleep, including the stages, deprivation, and importance. The benefits of sleep have been known for a long period of time and the recommended 8h is widely accepted. There is limited research into the importance of sleep for athletes, especially swimmers. There is also very little research into university athletes. It is important to understand the effect on student-athletes as their lifestyle, diet and general day-to-day life differ from elite athletes. The aim of the study was to investigate if quality of sleep affects swimming performance in university level swimmers. Ethical approval was given by the Northumbria University Faculty of Health and Life Science Ethics Committee. 11 student-athletes from the Northumbria University swimming team were recruited for the study. The sample size was determined by the size of the swimming team and those who volunteered. Participants completed a 50 and 200 m freestyle timed swim in the morning and the Pittsburgh Sleep Quality Index (PSQI) questionnaire. The times were compared between morning and evening, and between those deemed to have good quality sleep compared to poor quality sleep. The data was tested for normality and analysed using a paired t-test and Wilcoxon, depending on the normality of the data. For the 200 m swim, performance was quicker in the evening (P = 0.013). Eight out of the 11 swimmers (66%) were deemed to have poor quality sleep, one of those having a sleeping disorder. These results are in line with another study looking at the time of day on swimming performance (Nunes, et al. [2021]. Chronobiology International., 38, 1), where a significant difference was found in performance in a 400 m swim (between morning and evening), and no difference in a 50 m swim. As 66% of participants were found to have poor quality sleep, this highlights the importance of sleep and understanding the effects of sleep deprivation. The findings of the study reveal that the athletes performed better in the evening (18:00 hrs) compared to the morning (07:00 hrs). This is important when planning competitions and training programs. By understanding that athletes perform better in the evening when they’re more motivated and alert, coaches can plan more sessions in the evening than in the morning. This can also be considered for BUCS events, as the performance standard will be higher later in the day.